STRATEGI PERCEPATAN PENURUNAN STUNTING MELALUI INTERVENSI SENSITIF DI KECAMATAN SERANG - Hasanah, Neisa; Agustino, Leo; Cadith, Juliannes (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The high rate of stunting in Serang sub-district indicates the need for an accelerated reduction strategy based on data and a multi-sectoral approach. This study aims to formulate a strategy to accelerate stunting reduction through sensitive interventions that cover the health, education, and social infrastructure sectors. The theory used is Strategic Management and the Wheelen and Hunger approach, with a descriptive quantitative method and purposive sampling technique of 30 respondents from the Serang District Stunting Reduction Acceleration Team (TPPS). Data analysis was conducted using the IFE, EFE, IE Matrix, Cartesian diagram, and SWOT matrix. The results showed that Serang sub-district is in quadrant I (S-O) which recommends an aggressive strategy. Strengths include the active involvement of TPPS and community nutrition education, while opportunities come from national programmes and cross-sector support. The resulting priority strategies include optimising digital nutrition education, strengthening family assistance, and collaborating to improve sanitation. This research emphasises the importance of a local resource-based approach in formulating a sustainable stunting acceleration strategy.